Industrial training report: Jabatan Kerja Raya (JKR) Negeri Selangor / Farah Aqilah Badrul Hisham - Badrul Hisham, Farah Aqilah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Industrial training has become a common practice for students in all universities. Due to the concern of lack of experience after graduating, an internship can be the solution of the problem. Therefore, an information management students were required to complete a two-month internship during the semester break. Students were assisted by lecturers to search for a placement at an organization. Moreover, students were given a lecturer supervisor as the person to make sure the students were being well at their internship organization. Besides that, the lecturer supervisor was responsible for checking on their selected students by visiting students at the organization or making an online meeting. In this report, the student was accepted to do the internship at Jabatan Kerja Raya (JKR) Negeri Selangor in the ICT and Administration and Finance department. Some of suggestions and recommendations were given to improve the procedure of industrial training itself and the organization’s weaknesses.